The Mutation of International Law in Contemporary Constitutions: Thinking Sociologically about Political Constitutionalism. Issue 2 (March 2016) - Thornhill, Chris
Abstract : This article proposes a sociological critique of theories of political constitutionalism, which distinguish sharply between political and judicial constitutionalism and express hostility towards constitutions allowing extensive judicial control of legislation. It argues that such theories are usually undermined by a sociologically deficient account of politics. As an alternative, this article proposes a theory of politics based in a model of systemic inclusion . Using this perspective, it claims that constitutions with a strong judicial emphasis, especially where judicial functions are supported by international norms, have served, in many societies, as an effective precondition for the emergence and persistence of a relatively secure, differentiated political domain. These claims are exemplified through analysis of recent constitution‐making experiments in Russia, Kenya and Bolivia.